2014
DOI: 10.2298/sarh1406301z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in subgingival microflora after placement and removal of fixed orthodontic appliances

Abstract: Introduction. The placement of fixed orthodontic appliances may lead to increased plaque accumulation and changes in subgingival microflora. Objective. The aim of this study was to examine the changes in frequency of subgingival microflora that occur after placement and removal of fixed orthodontic appliance using polymerase chain reaction (PCR). Methods. This study included 33 orthodontic patients, who were divided into two groups. Subgingival plaque samples were collected from the right upp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 20 publications
0
25
0
1
Order By: Relevance
“…Three studies [1921] reported the microbial changes before and after appliance removal. Two studies [22, 23] analysed the effects of both appliance placement and removal on microbial changes. For a long-term observation, three studies [6, 15, 18] reported at least a 6-month observation period.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Three studies [1921] reported the microbial changes before and after appliance removal. Two studies [22, 23] analysed the effects of both appliance placement and removal on microbial changes. For a long-term observation, three studies [6, 15, 18] reported at least a 6-month observation period.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies [6, 16, 22] quantitatively evaluated the difference of the frequency of Aa in the first molar before and after appliance placement. The change was not statistically significant (odds ratio (OR), 0.82; 95% confidence interval (CI), 0.21–3.23; P  = 0.77) according to the meta-analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations